RETOLD: Review of the Meeting at Batavialand, Lelystad, September 2024 - Federico Cappadona (EXARC Journal)
This year between September 1-3, EXARC held a conference specifically focused on the topic of Digitalisation in Open-Air Museums and the cultural sector. Co-organised by the Batavialand Museum in Lelystad (the Netherlands), the event brought together the RETOLD partners and several professionals from around the world. RETOLD is a four-year project coordinated by EXARC and supported by the European Commission that aims to develop a documentation system designed for archaeological and ethnographic open-air museums.